Association of pazopanib-induced toxicities with outcome of patients with advanced soft tissue sarcoma; a retrospective analysis based on the European Organisation for Research and Treatment of Cancer (EORTC) 62043 and 62072 clinical trials. (3rd June 2019) - Vos, Melissa; Sleijfer, Stefan; Litière, Saskia; Touati, Nathan; Duffaud, Florence; van der Graaf, Winette T.; Gelderblom, Hans
Abstract: Background: There is an unmet need for markers predicting the outcome of patients with advanced soft tissue sarcoma (STS) treated with pazopanib. Since toxicity might be related to the anti-tumor activity of the drug, the aim of this study was to determine whether pazopanib-induced proteinuria, hypothyroidism and cardiotoxicity grade 3-4 were associated with outcome. Methods: The combined results of the EORTC 62043 and 62072 trials were retrospectively assessed and used in a landmark analysis to evaluate the effect of the toxicities on progression-free survival (PFS) and overall survival (OS), using the Kaplan-Meier method and Cox regression models. Results: Of the 333 eligible patients, 259 patients were included in the analyses, for which a landmark time point of 60 days after randomization/registration was selected. Proteinuria occurred in 25.1%, hypothyroidism in 22.0% and cardiotoxicity grade 3–4 in 5.8% of the patients (any grade in 41.7%). There was no effect of the occurrence of proteinuria (6-months PFS 35.4% for patients with vs. 38.3% for patients without proteinuria, HR 1.01, p  = .953), hypothyroidism (41.2% vs. 36.5%, HR 0.82, p  = .210) or cardiotoxicity grade 3–4 (26.7% vs. 38.2%, HR 0.97, p  = .897) on PFS. Nor was there an effect of proteinuria (6-months OS 63.2% for patients with vs. 74.4% for patients without proteinuria, HR 1.22, p  = .196), hypothyroidism (76.2% vs. 70.5%, HR 0.75, p  = .093) or cardiotoxicity grade 3–4 (80.0% vs. 77.2%, HR 0.93, p  = .801) on OS. Conclusion: There was no association between the occurrence of pazopanib-induced proteinuria, hypothyroidism and cardiotoxicity and outcome. Therefore, these toxicities cannot be used as predictors for pazopanib activity in patients with advanced STS.